2016
DOI: 10.1002/pd.4973
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal cfDNA screening results indicative of maternal neoplasm: survey of current practice and management needs

Abstract: A majority of counselors neither felt properly equipped nor comfortable counseling patients with prenatal cfDNA results suggestive of maternal neoplasm. This study demonstrates a need for collaboration amongst clinicians, researchers, and laboratories to publish data regarding NIPT results indicative of maternal neoplasm, and for the creation of management guidelines. © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Thus, cfDNA screening allows the assessment of prenatal genetic conditions far beyond those of routine prenatal screening to date. Newer applications are being introduced that will expand the amount of genetic information that can be collected and learned about the pregnancy (Dharajiya et al 2017;Xi et al 2017) as well as the health of the pregnant woman (Brison et al 2017;Giles et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, cfDNA screening allows the assessment of prenatal genetic conditions far beyond those of routine prenatal screening to date. Newer applications are being introduced that will expand the amount of genetic information that can be collected and learned about the pregnancy (Dharajiya et al 2017;Xi et al 2017) as well as the health of the pregnant woman (Brison et al 2017;Giles et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…13 Pre-test counseling has increasingly become an important aspect of NIPT, 14 and while genetic counselors almost always discuss the possibility of false positives and false negatives, a recent survey of genetic counselors revealed that only 55% of counselors communicated the possibility that NIPT may yield unexpected or rare results. 15 Similarly, 95% of counselors surveyed were aware that NIPT results may suggest maternal cancer; however, only 77% reported that they would disclose such results. 15 Interestingly, the same 77% indicated that they would disclose the information even if it were not included on the official NIPT report.…”
Section: Expanded Non-invasive Prenatal Testing: Advantages Challementioning
confidence: 99%
“…15 Similarly, 95% of counselors surveyed were aware that NIPT results may suggest maternal cancer; however, only 77% reported that they would disclose such results. 15 Interestingly, the same 77% indicated that they would disclose the information even if it were not included on the official NIPT report. 15 The majority of genetic counselors did not feel adequately equipped or comfortable counseling patients with NIPT results indicative of maternal cancer and 91.3% of them felt the need for institutional or national guidelines to manage such patients.…”
Section: Expanded Non-invasive Prenatal Testing: Advantages Challementioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that low fetal fraction may be associated with an increased risk for trisomy 18, trisomy 13, monosomy X, triploidy, and possibly other aneuploidies (32,46,47). Maternal karyotype abnormalities and occult maternal malignancy can also impact testing results, including copy number changes and whole chromosomal aneuploidies (48,49). For example, it has been estimated that up to 90% of women with 47,XXX are not aware of their aneuploidy (50,51).…”
Section: Biologic Preanalytical and Analytical Considerations For Cmentioning
confidence: 99%